Utilization of Jackfruit Seed Flour into Pan de Sal - Francis Wilton Arias; Marinelo Esmero; Jojemar Nolasco; Jehan Daizelle Poblador; Aiza Marie Seat (IC-ITECHS, 2022)
This study focuses on the Utilization of Jackfruit Seed Flour into Pan de sal. There are Fifty (50) community evaluators aged fifteen to sixty years old of Brgy. Sta. Rita, San Joaquin, Iloilo using convenience sampling method to determine the level of acceptability of Utilization of Jackfruit Seed Flour into Pan de Sal into three formulations as to its appearance, aroma, taste, texture and general acceptability. To determine if there are significance in the level of acceptability of Jackfruit seed flour as substitute in making Pan de Sal in threeformulation as to its appearance, aroma, taste, texture and general acceptability. The Sensory Evaluation sheet was used to determine the Five-Point Likert Scale to evaluate the sensory characteristics of the product and Five-Point Hedonic Scale for the general acceptability. Mean, Standard Deviation and ANOVA used as statistical tools. Result revealed that there was significant difference in the level of the acceptability of Jackfruit seed flour as substitute in making Pan de Sal to three formulation A, B, and C in terms of appearance, aroma, taste and texture. However, in terms of general acceptability, the result revealed that there was no significant difference in three (3) formulations. As to color, Formulation A (2.42%) results to light brown, Formulation B (3.76%) golden brown, formulation C (4.42%). As to aroma, Formulation A (2.00%) has no jackfruit seed aroma, Formulation B (4.00%) has moderate Jackfruit seed aroma and Formulation C (4.76%) has strong Jackfruit seed aroma. However, the acceptability level in terms of taste, Formulation A (2.00%) indicates there is no Jackfruit seed taste, while Formulation B (4.00%) has moderate Jackfruit seed taste and Formulation C (4.72%) indicates strong Jackfruit seed taste. As to texture, Formulation A (4.60%) is smooth, Formulation B (3.98%) is moderately smooth and Formulation C (3.44%) is moderately rough. As to its general acceptability, Formulation A (4.48%) like slightly, Formulation B (4.52%) liked very much and Formulation C (4.62%) as the highest. The following are the recommendations the farmers are recommended in giving significant value and importance for the full potential of Jackfruit tree plantation. The researchers are encouraged to do more research about the acceptability of Jackfruit seed flour that would supply with awareness and knowledge about the health benefits. Consumers are recommended to make snacks at home made of Jackfruit seed flour. Lastly, bakers are encouraged to use the Jackfruit seed flour because the result of this study would provide them new ideas and learning about the usage of it in creating a new product like Pan de Sal, cupcakes, cookies and among other baked products in the market.